Table of Content - - (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content: 1. The Beginnings and Endings of Hejaziyat Al-Sharif Al-Radi Dr. Khalid Hamid Mohammed Nuwaiher Alghanmi 2. Narrative temporal paradoxes in the "Shefrat Bilal" novel - an Applied study Laila Ahmed Abu Ajami, Etimad Ibrahim Hassan Al-Assad 3. The Semiotics of Titling in Very Short Poems: A Study of Contemporary Gulf Poetry Models. Musaad Kareem Jaber Aldhafeeri 4. The verbal act in the heritage text "the text of Ismail bin Abi Al-Jahm and Hisham bin Abdul Malik as a model" - a pragmatic study Dr. Rashid Hamoud Al-Farraj 5. 5. The dialectic of literary aesthetics between the old and the new: The theory of deviation as a model Dr. Jihad Faiz Al-Islam